2018
DOI: 10.1080/23794925.2018.1455545
|View full text |Cite
|
Sign up to set email alerts
|

Community Therapist Reports of Client Engagement Challenges During the Implementation of Multiple EBPs in Children’s Mental Health

Abstract: This study investigated therapist reports of client engagement challenges in delivering evidence-based practices (EBPs), within the context of a large-scale implementation of multiple practices in children’s mental health services. Data were drawn from an online survey of 668 therapists (88% female, 35.0% Non-Hispanic White). The majority of therapists (75.4%) endorsed at least one client engagement challenge during their implementation of an EBP with an identified client over the previous two months. Two type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 74 publications
2
23
3
Order By: Relevance
“…However, defining how therapists could have adapted a session may have altered reported frequencies of adaptations overall or for specific adaptation types. Yet, previous studies using survey methods in the current study context overall suggested similar patterns of more frequent Augmenting than Reducing adaptations and also allowed for the study of an additional category of Generalizing adaptations (Lau et al, 2018). Additional studies are needed to replicate findings on relative rates and contextual factors associated with adaptation types.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…However, defining how therapists could have adapted a session may have altered reported frequencies of adaptations overall or for specific adaptation types. Yet, previous studies using survey methods in the current study context overall suggested similar patterns of more frequent Augmenting than Reducing adaptations and also allowed for the study of an additional category of Generalizing adaptations (Lau et al, 2018). Additional studies are needed to replicate findings on relative rates and contextual factors associated with adaptation types.…”
Section: Discussionmentioning
confidence: 51%
“…Within the session survey, therapists completed a checklist indicating whether client‐related engagement challenges were encountered. Items assessing engagement challenges were adapted from the 2‐month retrospective report measure of client engagement challenges for an index case described in a previous study (Lau et al, 2018). In the current study, therapists reported on four items to indicate whether each engagement challenge had occurred.…”
Section: Methodsmentioning
confidence: 99%
“…Given that the majority (69.6%) of the clients participating in the study were Hispanic/ Latino, this finding may suggest that therapist ethnicity might have a bearing on client engagement and implementation outcomes, such that clients are more engaged in treatment when it is delivered by a therapist who they feel understands their culture (Berger et al 2014). In addition, therapist reports of Limited Client Engagement in Therapy Activities, but not Expressed Client Concerns, were related to a lower self-assessed ability to deliver the EBP (Lau et al 2018). These findings suggest that whereas limited client participation might portend barriers to EBP implementation, clients being comfortable or even invited to share their concerns about an intervention may not be associated with a therapist's compromised ability to deliver care as intended.…”
Section: Introductionmentioning
confidence: 95%
“…A recent study examined therapist perceptions of engagement challenges in the context of mandated EBP implementation (Lau et al 2018). Therapists reported on two types of engagement challenges encountered during the implementation of an EBP with a child client in the previous 2 months: Expressed Client Concerns and Limited Client Engagement in Therapy Activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation